2014
DOI: 10.1021/ja501789x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Catalytic Aerobic Oxidation of Phenols

Abstract: The oxidation of phenols is the subject of extensive investigation, but there are few catalytic aerobic examples that are chemo- and regioselective. Here we describe conditions for the ortho-oxygenation or oxidative coupling of phenols under copper (Cu)-catalyzed aerobic conditions that give rise to ortho-quinones, biphenols or benzoxepines. We demonstrate that each product class can be accessed selectively by the appropriate choice of Cu(I) salt, amine ligand, desiccant and reaction temperature. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
134
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(140 citation statements)
references
References 67 publications
2
134
0
4
Order By: Relevance
“…In 2013, Herres-Pawlis et al presented catalytic copper(I) model systems supported by bis(pyrazolyl)methane ligands which exhibit room temperature stable peroxo intermediates [20]. More recently, Lumb et al demonstrated catalytic conversions of different monophenols to a variety of organic products [21][22][23][24][25][26]. During the last years our group published a number of new copper(I) complexes functioning as model systems for tyrosinase [2,19,[27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Herres-Pawlis et al presented catalytic copper(I) model systems supported by bis(pyrazolyl)methane ligands which exhibit room temperature stable peroxo intermediates [20]. More recently, Lumb et al demonstrated catalytic conversions of different monophenols to a variety of organic products [21][22][23][24][25][26]. During the last years our group published a number of new copper(I) complexes functioning as model systems for tyrosinase [2,19,[27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The biological activity of a series of fullerenols C 60 (OH) [12][13][14] , C 60 (OH) [18][19][20][21][22][23][24] , C 60 (OH) [30][31][32][33][34][35][36][37][38] was studied by Eropkin and coworkers (3). Fullerenols C 60 (OH) [18][19][20][21][22][23][24] have revealed maximal biological activity (4,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, alcohol 6h was extremely susceptible to the acidity of the last step, and the SiMe 3 was replaced by H. Similar migrations have been reported to proceed by a radical mechanism. [56] In this case, the proposal is that once it is formed, the silylated phenol reacts by an electrophilic aromatic substitution reaction promoted by the hydroxyl group, at the ipso carbon of the trimethylsilyl substituent, leading to the formation of the observed product (i.e., 7g) and the release of TosO·SiMe 3 . The low yield of phenol 7i was unexpected, as we had observed that the reaction proceeded efficiently with alkyl groups and in presence of electronegative atoms in R…”
Section: Resultsmentioning
confidence: 99%